The fruit glossiness locus, dull fruit (D) encodes a C2H2 type zinc finger transcription factor CsDULL in cucumber (Cucumis sativus L.). Issue 1 (2nd July 2022) - Zhai, Xuling; Wu, Haoying; Wang, Yaru; Zhang, Zhongren; Shan, Li; Zhao, Xi; Wang, Ruijia; Liu, Chang; Weng, Yiqun; Wang, Ying; Liu, Xingwang; Ren, Huazhong
Abstract: Fruit glossiness is an important external fruit quality trait for fresh consumed cucumber fruit affecting its marketability. Dull fruit appearance is mainly controlled by a single gene, D (for dull fruit ) that is dominant to glossy fruit ( dd ), but the molecular mechanism controlling fruit glossiness is unknown. In the present study, we conducted map-based cloning of the D locus in cucumber and identified a candidate gene ( Csa5G577350 ) that encodes a C2 H2 type zinc finger transcription factor, CsDULL. A 4895 bp deletion including the complete loss of CsDULL resulted in glossy fruit. CsDULL is highly expressed in the peel of cucumber fruit, and its expression level is positively correlated with the accumulation of cutin and wax in the peel. Through transcriptome analysis, yeast one-hybrid and dual-luciferase assays, we identified two genes potentially targeted by CsDULL for regulation of cutin and wax biosynthesis/transportation that included CsGPAT4 and CsLTPG1 . The possibility that CsDULL controls both fruit glossiness and wart development in cucumber is discussed. The present work advances our understanding of regulatory mechanisms of fruit epidermal traits, and provides useful tool for molecular breeding to improve external fruit quality in cucumber.